Marek’s Disease Virus Modulates T Cell Proliferation via Activation of Cyclooxygenase 2-Dependent Prostaglandin E2 - Kamble, Nitin; Gurung, Angila; Kaufer, Benedikt B.; Pathan, Ansar Ahmed; Behboudi, Shahriar (Frontiers in Immunology, 2021)
Marek’s disease virus (MDV), an avian alphaherpesvirus, infects chickens, transforms CD4+ T cells, and induces immunosuppression early during infection. However, the exact mechanisms involved in MDV-induced immunosuppression are yet to be identified. Here, our results demonstrate that MDV infection in vitro and in vivo induces activation of cyclooxygenase-2 (COX-2) and production of prostaglandin E2 (PGE2). This exerts its inhibitory effects on T cell proliferation at day 21 post infection via PGE2 receptor 2 (EP2) and receptor 4 (EP4). Impairment of the MDV-induced T cell proliferation was associated with downregulation of IL-2 and transferrin uptake in a COX-2/PGE2 dependent manner in vitro. Interestingly, oral administration of a COX-2 inhibitor, meloxicam, during MDV infection inhibited COX-2 activation and rescued T cell proliferation at day 21 post infection. Taken together, our results reveal a novel mechanism that contributes to immunosuppression in the MDV-infected chickens